PENERAPAN MODEL PEMBELAJARAN MENCARI PASANGAN (MAKE A MATCH) DALAM MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS III-C SD NEGERI 1 CAKRANEGARA - ., SUKARTINI (Universitas Mahasaraswati Mataram, 2018)
This research is a Class Action Research (PTK) which has been implemented in SD Negeri 1 Cakranegara. Finding a mate (Make a Match) is a learning method that asks students to look for pairs of answer and question on cards in limited time, students who can match the card correctly will be given extra points. This learning method is applied to improve the learning outcomes of PKn subject of class III-C SDN 1 Cakranegara Semester II of the academic year 2017/2018 with the number of students as many as 34 people. To know the success rate of students test in the form of descriptions (essays) and multiple choice are used Collected data such as learning outcomes are analyzed descriptively. The analysis results of each cycle shows an increase in the average value of student learning outcomes. Average score of student learning outcomes in cycle I 70.47 and cycle II 79.44, increased by 8.97%, while the percentage of learning completeness in cycle I also increased from 67.65% to 82.35%. The results shows that the application of the learning method, to look for a partner (make a match), can improve students outcomes of grade III-C SD Negeri 1 Cakranegara